2016
DOI: 10.2147/copd.s54328
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian studies on pulmonary function in COPD patients: what are the gaps?

Abstract: BackgroundCOPD is a major cause of death and morbidity worldwide, and is characterized by persistent airflow obstruction. The evaluation of obstruction is critically dependent on sensitive methods for lung-function testing. A wide body of knowledge has been accumulated in recent years showing that these methods have been significantly refined and seems promising for detection of early disease.ObjectivesThis review focuses on research on pulmonary function analysis in COPD performed in Brazil during this centur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…In the presence of CLDs, changes in lung volume may exacerbate these defects. The loss of lung elastic recoil is a prominent feature of aging and a characteristic of asthma and COPD regardless of aging [23, 56-58]. CLDs in the elderly cause a significant decrease in lung function and blood oxygenation; these changes may impair the performance of skeletal muscles and result in loss of muscle strength and power [6].…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of CLDs, changes in lung volume may exacerbate these defects. The loss of lung elastic recoil is a prominent feature of aging and a characteristic of asthma and COPD regardless of aging [23, 56-58]. CLDs in the elderly cause a significant decrease in lung function and blood oxygenation; these changes may impair the performance of skeletal muscles and result in loss of muscle strength and power [6].…”
Section: Resultsmentioning
confidence: 99%
“… 7 11 Assessment of respiratory obstruction in the early stages is critically dependent on the sensitivity of pulmonary function tests. 12 It has previously been observed that spirometric indices are not sensitive to small changes due to smoking. 13 …”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, there have been significant technological advances in tools used to measure lung function. Despite the technological sophistication of traditional functional assessment methods, new PFTs are gradually being incorporated into clinical practice ( 6 ). There has been growing interest in the use of the single-breath washout (N 2 SBW) test because it is a simple, non-invasive tool and can detect heterogeneity in the ventilation distribution and small airway disease in cases in which traditional PFTs indicate normal values ( 7 ).…”
Section: Introductionmentioning
confidence: 99%